11 million from SAMHSA to train first responders and community groups on preventing OD deaths. Issue 33 (20th August 2021) - Knopf, Alison
Abstract : Last week, the Substance Abuse and Mental Health Services Administration (SAMHSA) distributed 11 million in grants to train first responders and community groups to prevent overdose deaths. The 13 grants were in training to administer naloxone.